Expression of matrix macromolecules and functional properties of breast cancer cells are modulated by the bisphosphonate zoledronic acid - Dedes, P.G.; Gialeli, Ch; Tsonis, A.I.; Kanakis, I.; Theocharis, A.D.; Kletsas, D.; Tzanakakis, G.N.; Karamanos, N.K. (Biochimica et biophysica acta, 2012)
The extracellular matrix (ECM) components play key roles in the multistep process of cancer growth and progression. Preclinical and clinical data show that bisphosphonates (BPs) may exert direct or indirect antitumoral effects. Despite proven efficiency in cancer treatment, the mechanism by which BPs can interfere with cancer progression remains elusive. We investigated the effects of the third generation BP, zoledronate (zoledronic acid, Zometa®), in the expression of ECM macromolecules as well as the functional properties (proliferation, adhesion, migration and invasion) in two breast cancer cell lines (MDA-MB-231 and MCF-7) with different metastatic potentials. The data highlight that zoledronate effectively inhibits growth of breast cancer cells, functional invasion migration and adhesion to various matrices. At the level of ECM interacting molecules, the expression of specific heparan sulfate proteoglycans implicated in cancer progression, such as syndecan-1, -2 and glypican-1 is downregulated, whereas syndecan-4 expression is upregulated upon treatment with zoledronate. The levels of integrins ανβ3, ανβ5 and α5β1 were significantly reduced following treatment with zoledronate which is in accordance with the reduced cell adhesion on various ECM matrices. The expression of hyaluronan and its receptor CD44 was also significantly suppressed. Moreover, ZOL suppressed the expression of metalloproteinases MMP-2, -9, the membrane type MT1- and MT2-MMP, whereas it increased the expression of their endogenous tissue inhibitors. The obtained results demonstrate that zoledronate is a critical modulator of ECM gene expression and powerful anticancer agent inhibiting growth, migration and the matrix-associated invasion of breast cancer cells. ► Zoledronate inhibits invasion, migration and adhesion of breast cancer cells. ► Modulates the expression of matrix molecules implicated in cancer progression. ► Potent pharmaceutical anticancer agent for breast cancer.